Safety Aspects, Tolerability and Modeling of Retinofugal Alternating Current Stimulation - Haberbosch, Linus; Datta, Abhishek; Thomas, Chris; Jooß, Andreas; Köhn, Arvid; Rönnefarth, Maria; Scholz, Michael; Brandt, Stephan A.; Schmidt, Sein (Frontiers in Neuroscience, 2019)
Background While alternating current stimulation (ACS) is gaining relevance as a tool in research and approaching clinical applications, its mechanisms of action remain unclear. A review by Schutter and colleagues argues for a retinal origin of transcranial ACS’ neuromodulatory effects. Interestingly, there is an alternative application form of ACS specifically targeting α-oscillations in the visual cortex via periorbital electrodes (retinofugal alternating current stimulation, rACS). To further compare these two methods and investigate retinal effects of ACS, we first aim to establish the safety and tolerability of rACS. Objective The goal of our research was to evaluate the safety of retinofugal alternating current stimulation (rACS) via finite-element modeling, theoretical safety limits and subjective report. Methods 20 healthy subjects were stimulated with rACS as well as photic stimulation and reported adverse events following stimulation. We analyzed stimulation parameters at electrode level as well as distributed metric estimates from an ultra-high spatial resolution magnetic resonance imaging (MRI)-derived finite element human head model and compared them to existing safety limits. Results Topographical modeling revealed the highest current densities in the anterior visual pathway, particularly retina and optic nerve. Stimulation parameters and finite element modeling estimates of rACS were found to be well below existing safety limits. No serious adverse events occurred. Conclusion Our findings are in line with existing safety guidelines for retinal and neural damage and establish the tolerability and feasibility of rACS. In comparison to tACS, retinofugal stimulation of the visual cortex provides an anatomically circumscribed model to systematically study the mechanisms of action of ACS.